Remote monitoring of outpatients discharged from the emergency cardiac care department - A. A. Garanin; I. S. Mullova; O. V. Shkaeva; P. D. Duplyakova; D. V. Duplyakov (Российский кардиологический журнал, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has shown the need for the development of telemedicine technologies, especially remote follow-up using vital sign telemonitoring. In the Russian Federation, this approach is also justified by the remoteness factor with a shortage of medical workers in distant areas of the country.Aim. To study the potential of remote monitoring in outpatients discharged after acute decompensated heart failure and acute coronary syndrome.Material and methods. The study included 392 patients randomized to active follow-up groups with remote blood pressure (BP) monitoring (group 1, n=197) and standard management (group 2, n=195). The follow-up period lasted 3 months.Results. During the follow-up period, patients managed with BP and heart rate telemonitoring tended to decrease in systolic BP from 132 (interquartile range (IQR), 121-139) mm Hg up to 125 (IQR, 115-130) mm Hg (p=ns). On the contrary, the 2nd group patients had a slight increase in systolic BP from 127 (IQR, 115-137) mm Hg up to 132 (IQR, 124-142) mm Hg (p=ns).The patients of group 2 were more likely to receive diuretics and nitrates after 3-month follow-up, which can be considered a negative factor. This may indicate no improvement in the course of heart failure and chronic coronary artery disease with the absence of therapy correction over time.During follow-up, four patients from group 1 were hospitalized due to decompensated heart failure or an episode of acute coronary syndrome with a total duration of 30 days, compared with 13 hospitalizations for the same reasons in group 2 (p=0,027; OR 3,4; 95% CI 1,1-10,8). In total, six patients died during the follow-up period in group 1, and eleven patients died in group 2 (p=0,226; OR 1,9; 95% CI 0,7-5,3). At the same time, three patients in the 1st group and one patient from the 2nd group died during the follow-up period due to COVID-19. Thus, cardiovascular mortality consisted of 3 and 10 patients in groups 1 and 2, respectively (p=0,052; OR 3,5; 95% CI 0,9-12,9).Conclusion. Three-month remote management of patients after decompensated heart failure or acute coronary syndrome, including BP monitoring, showed a significant reduction in the hospitalization rate and a trend towards a decrease in cardiovascular mortality.